Starobinsky-like inflation and soft-SUSY breaking - Stephen F. King (Journal of High Energy Physics, 2019)
Abstract We study a version of Starobinsky-like inflation in no-scale supergravity (SUGRA) where a Polonyi term in the hidden sector breaks supersymmetry (SUSY) after inflation, providing a link between the gravitino mass and inflation. We extend the theory to the visible sector and calculate the soft-SUSY breaking parameters depending on the modular weights in the superpotential and choice of Kähler potential. We are led to either no-scale SUGRA or pure gravity mediated SUSY breaking patterns, but with inflationary constraints on the Polonyi term setting a strict upper bound on the gravitino mass m 3/2 < 103 TeV. Since gaugino masses are significantly lighter than m 3/2, this suggests that SUSY may be discovered at the LHC or FCC.